(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
In this article, drawn from my ongoing doctoral research, I explore the evolving phenomenology of borderline personality disorder and consider the possible relevance of the experience of existential isolation to our understanding of individuals with this diagnosis.